Design and Development of a Vertical Paddle Semi Automated Garri Frying Machine - C.P. Nwadinobi; J.C. Edeh; K.I. Mejeh (Journal of Applied Sciences and Environmental Management)
Garri frying is the most critical unit operation in the processing of cassava into garri. The quality of the final product is much dependent on this processing stage which is a combination of simultaneous cooking and drying processes. This work presents the development of a garri fryer and the performance evaluation of the machine at various operational parameters. The fryer throughput capacity, (TP)c and functional/drying efficiency, were used to evaluate the performance of the fryer. The cooking and drying performance of the developed machine accounted for throughput capacity of 20.66kg/hr and functional efficiency of 66%. In addition, a preferred final moisture content of 12.14%w.b. was achieved at 20rpm paddle speed and frying time of 23 minutes. The equipment have addressed the short coming observed in the village technique such as time-consumption, health hazard for the operator. In addition, it is user friendly as it requires no skilled labour and also uses different heat sources for convenience of the user.